2006
DOI: 10.1634/stemcells.2006-0235
|View full text |Cite
|
Sign up to set email alerts
|

Nucleofection Is a Valuable Transfection Method for Transient and Stable Transgene Expression in Adipose Tissue-Derived Stem Cells

Abstract: STEM CELLS 2007;25:790 -797

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 31 publications
6
42
0
1
Order By: Relevance
“…hMADS cell culturing and differentiation hMADS-3 cells (Rodriguez et al 2005;Zaragosi et al 2007) were cultured and differentiated into mature adipocytes as described in the Supplemental Material. From day 13 to day 16 of differentiation, hMADS adipocytes were treated with rosiglitazone to form brite adipocytes or with DMSO to maintain white adipocytes.…”
Section: Methodsmentioning
confidence: 99%
“…hMADS cell culturing and differentiation hMADS-3 cells (Rodriguez et al 2005;Zaragosi et al 2007) were cultured and differentiated into mature adipocytes as described in the Supplemental Material. From day 13 to day 16 of differentiation, hMADS adipocytes were treated with rosiglitazone to form brite adipocytes or with DMSO to maintain white adipocytes.…”
Section: Methodsmentioning
confidence: 99%
“…While others showed the percentage of cells exhibiting green fluorescent protein reporter gene (Aluigi et al 2006;Zarogasi et al 2007), we measured the mean intensity of luciferase reporter gene in viable cells using the pRL-CMV plasmid DNA. Our results showed that the mean expression in viable hMSC was four times higher (21.79%) when the U-23 pulsing program was used compared with C-17 (5.62%).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the apoptosis and the low cell density, mesenchymal cells lost their chondrifying characteristics, therefore detection of metachromasial extracellular matrix was almost impossible on the last day of culturing (day 6). Thus, although electroporation gives high transfection efficiency on different cell lines [39,40] it does not seem applicable to deliver vectors into primary mesenchymal chondrifying cell cultures.…”
Section: Discussionmentioning
confidence: 99%